Daya Hasil Dan Adaptasi Lima Varietas Kedelai Di Kecamatan Prafi, Kabupaten Manokwari - Yohanes S.B.; Theresia Tan (Fakultas Pertanian Universitas Papua, 2009)
The objective of this experiment was to determine productivity and adaptation of five varieties of soybean in Manokwari. The experiment was conducted at Prafi (SP4)Manokwari using completely randomized block design consisting of 5 varieties of soybean (Lokon, Wilis, Galunggung, Nakon Sawon and Local Prafi) as a treatment in three replicates.The results showed that all superior varieties (Lokon, Wilis and Galunggung) had good adaptation to be developed at Prafi, Manokwari for increasing soybean production. Productivity per hectar of all tested varieties were 1.35 ton (Lokon), 1.09 ton (Wilis), 1.02 ton (Galunggung), 0.72 ton (Local Prafi) and only 0.22 ton for Nakon Sawon. Nakon Sawon variety is not recommended to be developed as it had the lowest yield for all variables observed and had low resistance to be attacked by pests and diseases.